2021
DOI: 10.4193/rhin21.037
|View full text |Cite
|
Sign up to set email alerts
|

Olfaction in COPD

Abstract: Background: Olfaction is poorly characterized in COPD. To test the hypothesis that olfaction is reduced in COPD, we assessed olfaction with the “Sniffin’ Sticks” test and a questionnaire addressing olfaction in COPD and a corresponding control group in respect to age and sex. We also explored whether there is an association between COPD, chronic rhinosinusitis without nasal polyps (CRSsNP), and other predefined covariates with olfactory function. Methodology: Olfactory function was assessed by the score for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Gender differences in human olfaction in the general population have been widely discussed in the literature, with most of the studies confirming our observation of a female superiority in olfactory perception [35,36]. Several data suggest that neuroendocrine, social and cognitive elements may play a major role in this context [37,38]. In this context, previous studies have shown that OD is one of the first symptoms in several neurodegenerative diseases, such as Parkinson's disease and Alzheimer's disease, and appears years before motor symptoms and cognitive decline clinically manifest, which demonstrated that cognitive pathways play a major role in the pathogenesis of OD [39].…”
Section: Discussionsupporting
confidence: 86%
“…Gender differences in human olfaction in the general population have been widely discussed in the literature, with most of the studies confirming our observation of a female superiority in olfactory perception [35,36]. Several data suggest that neuroendocrine, social and cognitive elements may play a major role in this context [37,38]. In this context, previous studies have shown that OD is one of the first symptoms in several neurodegenerative diseases, such as Parkinson's disease and Alzheimer's disease, and appears years before motor symptoms and cognitive decline clinically manifest, which demonstrated that cognitive pathways play a major role in the pathogenesis of OD [39].…”
Section: Discussionsupporting
confidence: 86%
“…Indeed, a comorbidity between SCZ and lung diseases have been reported, and in both directions: schizophrenia was found to be associated with impaired lung function (43), and patients with COPD have 10 times higher risk of psychiatric comorbidities (44). There are reports that olfactory deficits\ known to be prevalent in SCZ are also found in most COPD patients (45). We hypothesize that alterations in the properties of mesenchymal cells may contribute to a range of "mesenchymal" disorders, which include some subtypes of schizophrenia and lung diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a comorbidity between SCZ and lung diseases has been reported, and in both directions, schizophrenia was found to be associated with impaired lung function [42], and patients with COPD have a 10 times higher risk of psychiatric comorbidities [43]. There are reports that olfactory deficits known to be prevalent in SCZ are also found in most COPD patients [44]. We hypothesize that alterations in the properties of mesenchymal cells may contribute to a range of "mesenchymal" disorders, which include some subtypes of schizophrenia and lung diseases.…”
Section: Discussionmentioning
confidence: 99%